# (3-a)+1=5(a-9)+3

## Simple and best practice solution for (3-a)+1=5(a-9)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (3-a)+1=5(a-9)+3 equation:

(3-a)+1=5(a-9)+3
We move all terms to the left:
(3-a)+1-(5(a-9)+3)=0
We add all the numbers together, and all the variables
(-1a+3)-(5(a-9)+3)+1=0
We get rid of parentheses
-1a-(5(a-9)+3)+3+1=0

We calculate terms in parentheses: -(5(a-9)+3), so:
5(a-9)+3
We multiply parentheses
5a-45+3
We add all the numbers together, and all the variables
5a-42
Back to the equation:
-(5a-42)

We add all the numbers together, and all the variables
-1a-(5a-42)+4=0
We get rid of parentheses
-1a-5a+42+4=0
We add all the numbers together, and all the variables
-6a+46=0
We move all terms containing a to the left, all other terms to the right
-6a=-46
a=-46/-6
a=7+2/3

`